Detection and Localization of Solid Tumors Utilizing the Cancer-Type-Specific Mutational Signatures - Wang, Ziyu; Zhang, Tingting; Wu, Wei; Wu, Lingxiang; Li, Jie; Huang, Bin; Liang, Yuan; Li, Yan; Li, Pengping; Li, Kening; Wang, Wei; Guo, Renhua; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Accurate detection and location of tumor lesions are essential for improving the diagnosis and personalized cancer therapy. However, the diagnosis of lesions with fuzzy histology is mainly dependent on experiences and with low accuracy and efficiency. Here, we developed a logistic regression model based on mutational signatures (MS) for each cancer type to trace the tumor origin. We observed MS could distinguish cancer from inflammation and healthy individuals. By collecting extensive datasets of samples from ten tumor types in the training cohort (5001 samples) and independent testing cohort (2580 samples), cancer-type-specific MS patterns (CTS-MS) were identified and had a robust performance in distinguishing different types of primary and metastatic solid tumors (AUC:0.76 ~ 0.93). The metastatic tumor lesions inherited the MS pattern of the primary tumor, suggesting the capability of MS in identifying the tissue-of-origin for metastatic cancers. Furthermore, we distinguished breast cancer and prostate cancer with 90% accuracy by combining somatic mutations and CTS-MS from cfDNA, indicating that the CTS-MS could improve the accuracy of cancer-type prediction by cfDNA. In summary, our study demonstrated that MS was a novel reliable biomarker for diagnosing solid tumors and provided new insights into predicting tissue-of-origin.